MARKETING OF NON-PROFITS OF EDUCATION AND RESEARCH SECTOR OF UKRAINE: CONCEPTUAL PECULIARITIES AND VECTORS OF DEVELOPMENT - Borysova, Tetiana (Journal of European Economy, 2017)
The problem of marketization of education and research NPOs in the context of Ukrainian financial paradigm has been elucidated in the article. It has been proved that the following areas of marketing activity are relevant for the domestic business education and research: increased market orientation of non-profit education and research, as market orientation is applicable for Ukrainian universities though it is not always carried out properly; development of markets (one of the directions of the educational markets both in Ukraine and Europe is lifelong learning and adult education, the latter, however, is not wide spread in Ukraine, the development of distance learning, attracting foreign students from less developed countries); organization of effective marketing in order to improve the quality of education and reduce the gap between the supply of educational services market and demand in the labor market. The analysis of definitions of «marketing of educational organizations» has revealed some similarities as well as own definition has been suggested. A number of peculiar features of the elements of the complex of marketing of educational organizations have been presented.